Ultrahigh electron-deficient pyrrolo-acenaphtho-pyridazine-dione based donor–acceptor conjugated polymers for electrochromic applications. Issue 43 (15th September 2015) - Cho, Ching Mui; Ye, Qun; Neo, Wei Teng; Lin, Tingting; Lu, Xuehong; Xu, Jianwei
Abstract : New ultrahigh electron-deficient acceptors pyrrolo-acenaphtho-pyridazine-diones (PAPD) were synthesized via a regio-selective inverse electron demand Diels–Alder reaction and their corresponding conjugated polymers showed electrochromism with long-term stability. Abstract : Novel electron acceptors 2-alkyl-6, 9-di(thiophen-2-yl)-1 H -pyridazino[4′, 5′:2, 3]indeno[6, 7, 1- def ]isoquinoline-1, 3(2 H )-dione and 2-alkyl-6, 9-di(furan-2-yl)-1 H -pyridazino[4′, 5′:2, 3]indeno[6, 7, 1- def ]isoquinoline-1, 3(2 H )-dione derived from pyrrolo-acenaphtho-pyridazine-diones (PAPD) with a very low-lying lowest unoccupied molecular orbital (LUMO) level have been synthesized via a regioselective inverse electron demand Diels–Alder reaction between thiophene- and furan-substituted 1, 2, 4, 5-tetrazine and an electron-deficient compound 2-(2-alkyl)-1 H -indeno[6, 7, 1- def ]isoquinoline-1, 3(2 H )-dione. The chemical structures of two PAPD monomers were confirmed by 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry as well as single-crystal X-ray structural analysis. The time-dependent density functional theory (TD-DFT) calculations were performed to show that PAPD series monomers have a LUMO energy level down to −3.42 eV, much lower than the popular electron acceptors such as benzotriazole, benzothiadiazole and its fluorinated derivatives (−2.19–−2.98 eV). The PAPD based monomer was incorporated into a series of donor–acceptor type conjugated polymers comprising 3, 3-bis((dodecyloxy)methyl)-3, 4-dihydro-2 H -thieno[3, 4- b ][1, 4]dioxepine and thieno[3, 2- b ]thiophene as co-monomers through Stille coupling polymerization to give electrochromic conjugated polymersP1–P5 with high number-average molecular weights in the range of 42 000–67 000 (g mol −1 ). The polymers showed optical bandgaps between 1.90–1.99 eV. Electrochromic devices displayed reversible color changes between purple/red in the neutral state and greyish blue/grey in the oxidized state with an outstanding redox stability of less than 1% decrease in contrast after 800 cycles using polymerP3 as an example, and high optical contrasts of up to 80% at 1500 nm in the near infrared region.